Vancomycin resistance is overcome by conjugation of polycationic peptides - Umstätter, Florian; Domhan, Cornelius; Hertlein, Tobias; Ohlsen, Knut; Mühlberg, Eric; Kleist, Christian; Zimmermann, Stefan; Beijer, Barbro; Klika, Karel D.; Haberkorn, Uwe; Mier, Walter; Uhl, Philipp (Angewandte Chemie. International edition, 2020)
Resistance is futile: By site-specific conjugation polycationic peptides were conjugated to vancomycin. Derivatives that bear the peptide moiety at four different sites of the antibiotic were synthesized.